Generalized and multiplexed q-plates emulated via an LCoS-based device - Vergara, Martín Alexis (2021)
In this paper we implement a previously proposed experimental device based on a liquid crystal on silicon (LCoS) display for emulating generalized q-plates. In order to prove the feasibility of this method, we test q-plates defined by linear and nonlinear functions of both the radial and the azimuthal variables, and study their effect on uniformly polarized beams in the near and far-field regime. This gives a tool for achieving beams with hybrid states of polarization (SoPs), and alternative phase and intensity distributions. We also propose an application that takes advantage of the pixelated nature of this kind of devices for creating arbitrary superpositions of vector and vortex beams by emulating randomized combinations of two different q-plates, i.e. multiplexed q-plates. Great agreement is found between theoretical and experimental results.